Cultural Sensitivity in Language Education: Methods and Best Practices - Aisyah, Aisyah; Rocha, Thiago; Silva, Pedro (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2024)
Cultural sensitivity in language education is essential for fostering inclusive and effective learning environments. Language learning involves not only acquiring linguistic skills but also understanding the cultural context in which language is used. However, many language education programs overlook the importance of cultural sensitivity, which can impact student engagement and comprehension. This research aims to identify effective methods and best practices for integrating cultural sensitivity into language education, enhancing both linguistic and intercultural competence among learners. A qualitative research approach was employed, involving case studies and interviews with 30 language educators from diverse educational institutions. Data was collected to explore educators’ experiences and strategies for incorporating cultural sensitivity into their teaching. The study also analyzed classroom practices to determine which methods were most effective in fostering cultural awareness. Thematic analysis was conducted to identify common practices and challenges faced by educators in implementing culturally sensitive teaching strategies. The findings reveal that integrating cultural sensitivity into language education leads to higher student engagement, deeper understanding of cultural context, and improved language proficiency. Best practices identified include the use of culturally relevant materials, facilitating discussions around cultural diversity, and encouraging students to share their own cultural backgrounds. Educators noted that these practices not only enhance language skills but also build students’ empathy and openness toward diverse cultures. This study concludes that culturally sensitive methods are essential for effective language education, providing students with the skills needed for meaningful intercultural communication. Future research should focus on developing scalable frameworks to support culturally sensitive teaching across varied educational contexts.